Morphometric and condition analysis of Asian horseshoe crabs from kelong-based fishing encounters in North Kalimantan, Indonesia - MOHAMMAD FADNAN AKHMADI; SUTRISNO ANGGORO; AGUS SABDONO; ANINDITIA SABDANINGSIH; RUKISAH RUKISAH; ENCIK WELIYADI; NURIL FARIZAH (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Akhmadi MF, Anggoro S, Sabdono A, Sabdaningsih A, Rukisah, Weliyadi E, Farizah N. 2026. Morphometric and condition analysis of Asian horseshoe crabs from kelong-based fishing encounters in North Kalimantan, Indonesia. Biodiversitas 27 (7): d270719. https://doi.org/10.13057/biodiv/d270719. Asian horseshoe crabs are conservation-relevant coastal arthropods, but biological baseline information from North Kalimantan, Indonesian Borneo, remains limited. This study analyzed species-specific morphometry, length-weight scaling, body condition, body proportion, and sexual dimorphism of Carcinoscorpius rotundicauda, Tachypleus gigas, and Tachypleus tridentatus. A total of 205 individuals (C. rotundicauda, n: 109; T. gigas, n: 75; T. tridentatus, n: 21) were recorded during 16 fisher-assisted kelong encounters at four coastal stations from January to April 2025. Each individual was identified, sexed, measured, weighed, recorded by station and sampling period, photographed, and released alive after handling. Clear interspecific size differentiation was observed, with T. tridentatus being the largest and heaviest species, C. rotundicauda the smallest, and T. gigas intermediate in size. Species-specific length-weight analysis indicated isometric scaling for T. gigas. The T. tridentatus length-weight estimate was also consistent with isometry but should be considered preliminary, whereas the C. rotundicauda total-length model had low explanatory power and was sensitive to telson condition. Fulton’s condition factor differed among species, while relative condition factor was interpreted mainly within species because it was derived from species-specific equations. Females tended to be larger and heavier than males, but the sex-specific findings for T. tridentatus are preliminary because of its small sample size. Because fishing effort and capture probability were not standardized and repeat encounters could not be excluded, the results describe recorded individuals and should not be interpreted as estimates of abundance, recruitment, catch per unit effort, habitat preference, or population structure. This study provides an integrated morphometric and condition baseline for all three extant Asian horseshoe crab species within a single North Kalimantan kelong-encounter dataset.